Impact of smoking on nasal mucociliary clearance time in Kano metropolis, Nigeria - Ahmad Mahmud; Abubakar D. Salisu; Emmanuel S. Kolo; Muhammad G. Hasheem; Nafisatu Bello‐Muhammad; Ahmad R. Tukur; Yasir J. Nuhu; Rabiu I. Jalo (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2023)
Abstract Background Mucociliary clearance is an important defense mechanism in human upper and lower respiratory airways. Impairment of this process by certain conditions such as cigarette smoking can predispose to chronic infection and neoplasm of the nose and paranasal sinuses. Methods This was a cross‐sectional study conducted in Kano metropolis, Nigeria. Eligible adults were enrolled, a saccharine test was conducted, and the nasal mucociliary clearance time was assessed. Analysis of the result was carried out using Statistical Product and Service Solutions version 23.0. Results There were 225 participants categorized into 75 active smokers (33.3%), 74 passive smokers (32.9%), and 76 nonsmokers (33.8%, living in a smoking‐free zone). The age range of the participants was between 18 and 50 years, with a mean age of (31.2 ± 5.6) years. All participants were males. There were 139 (61.8%) of Hausa‐Fulani ethnic group, 24 (10.7%) Yoruba, 18 (8.0%) Igbo, and 44 (19.5%) other ethnic groups. Findings in this study showed that the average mucociliary clearance time among active smokers was prolonged ([15.25 ± 6.20] min) compared to passive ([11.41 ± 4.25] min) and nonsmokers ([9.17 ± 2.76] min) respectively, with a statistical significance (F = 33.59, P < 0.001). Binary logistic regression revealed that the number of cigarettes smoked per day was an independent predictor of prolonged mucociliary clearance time (P = 0.008, odds ratio = 0.44, 95% confidence interval = 0.24–0.80). Conclusion Active cigarette smoking is associated with prolonged nasal mucociliary clearance time. The number of cigarette sticks smoked per day was found to be an independent predictor of prolonged mucociliary clearance time.